PEMANFAATAN TEPUNG KIMPUL (Xanthosoma sagittifolium) DAN TEPUNG TAPIOKA PADA PEMBUATAN BISKUIT - Yeffy Tidore; Dr.Ir. Christine F. Mamuaja, MS.; Ir. Teltje Koapaha, MP. (Universitas Sam Ratulangi, 2017)
AbstractUTILIZATION OF FLOUR CONTROL (Xanthosoma sagittifolium) AND TAPIOCA FLOUR IN BISCUITS MAKINGUtilization of kimpul flour and tapioca flour in the processing of various cakes can reach 100%, depending on the product to be produced. Biscuits are one snack or a snack that is widely consumed by people, and generally contain carbohydrates, protein and fat. The purpose of this research is to know the consumer acceptance level in term of color, odor, taste and crispness and to obtain proximate composition, calorific value and also determine the best formulation for biscuit making. This research was conducted for three months (November 2016 - januari 2017) in Food science laboratory of Agriculture Faculty. Sam Ratulangi University Manado. This research used completely randomized design method (RAL). The result showed that the research was the most preferred treatment that promical that the most prefred biscuits in term of: aroma, color, flavor, and crispness, namely the treatment of 30% kimpul flour and 70% tapioca flour, with chemical composition of water of wash, ash, protein, fat, carbohydrate and calories were 2.97%, 1.56%, 6.69%, 17.21%, 71.56% and 467.89 ccal, respectively.Keywords: Biscuits, Flour, Kimpul, Tapioca